Analysis Of Shooting Ability Of Futsal Extracurricular Students At SMA Negeri 5 Seluma Regency - Saputra, Yengki Hajis; Anggara, Deffri; Banat, Azizatul (Jurnal Multidisiplin, 2024)
Shooting is the process of kicking the ball hard and accurately. The success in kicking an accurate goal cannot be separated from the strength of the legs and the right kicking position. In the extracurricular futsal participants of SMA Negeri 5 Seluma Regency, there has been no research on the analysis of shooting ability in members or participants of extracurricular futsal. The purpose of this study was to determine the shooting skills of extracurricular futsal participants of SMA Negeri 5 Seluma Regency. This research is quantitative research, where the purpose of this research is to provide a description of the existing reality about the analysis of shooting ability in extracurricular futsal participants of SMA Negeri 5 Seluma Regency. The instrument test used shooting with a distance of 10 M with repeated shooting 10 times and the score in the goal. This study used purposive sampling techniques totalling 20 people. Data analysis looking for the percentage of each data with the percentage formula After the data is obtained from the test results, the next step is to process it with statistical formulas. These data processing steps are obtained by procedure. The results of this study are shooting ability in extracurricular participants of SMA Negeri 5 Seluma Regency, based on the ‘Excellent’ category with a percentage of 0% (0 people). Category ‘Good’ with a percentage of 0% (0 people). ‘Medium’ category with a percentage of 10% (2 people). ‘Less’ category with a percentage of 90% (18 people). Category ‘Very Poor’ 0% (0 people). These results can be interpreted that the shooting ability of extracurricular futsal participants at SMA Negeri 5 Seluma Regency is lacking, this makes SMA Negeri 5 Seluma Regency futsal experience a decline in its achievements in events and tournaments between high schools in Seluma Regency.